2018
DOI: 10.1617/s11527-018-1220-1
|View full text |Cite
|
Sign up to set email alerts
|

Design considerations of high RAP-content asphalt produced at reduced temperatures

Abstract: In many countries recycling of reclaimed asphalt pavement (RAP) for road surface layers is limited to a maximum of 10-30%. This is due to technical limitation of common asphalt plant but also to specifications that are still restrictive when it comes to increasing RAP in surface courses. The mistrust in this practice is mainly related to uncertainty in performance of these mixes as well as to existing fundamental issues with the mix design, especially when production temperatures are lowered. This paper analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…Binder replacement ratios of 13.02%, 21.6%, and 38.37% were found for mixes with 15%, 25%, and 45% RAP contents, respectively. It should be noted that the mixing conditions were optimized as suggested by Abed et al [34] to maximize the degree of blending DOB between virgin and RAP binders so that the full blending assumption is reasonable. In this context, the mixing time was extended to 6 min for all mixes and the mixing temperature was maintained at 135 • C for warm asphaltic mixtures.…”
Section: Methodsmentioning
confidence: 99%
“…Binder replacement ratios of 13.02%, 21.6%, and 38.37% were found for mixes with 15%, 25%, and 45% RAP contents, respectively. It should be noted that the mixing conditions were optimized as suggested by Abed et al [34] to maximize the degree of blending DOB between virgin and RAP binders so that the full blending assumption is reasonable. In this context, the mixing time was extended to 6 min for all mixes and the mixing temperature was maintained at 135 • C for warm asphaltic mixtures.…”
Section: Methodsmentioning
confidence: 99%
“…With a growing amount of milled RAP in developed countries, techniques and technologies that allow the highest possible percentage (up to 100%) of the RAP in the recycled asphalt mixture are developed [52]. Design considerations of high RAP-content asphalt produced at reduced temperatures were described by Abed et al [53]. However, the results of the study suggested that the full blending hypothesis is unpractical for the sake of asphalt plant productivity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, when pavement suffers severe distress and, as a result, no longer functions with satisfactory quality, pavement has to be reconstructed [ 1 ]. On the other hand, to address increased environmental concerns, an economic solution to deal with reclaimed asphalt pavement (RAP) is to reuse recycled materials in construction [ 2 ]. Specifically, a certain amount of RAP can be incorporated into the production of new asphalt mixtures, aiming to reduce resource consumption.…”
Section: Introductionmentioning
confidence: 99%